Using RCRR Strategy to Improve Students’ Reading Comprehension Skill - Mutia, Utin; Desvy, Ewa; Novrieta, Dina; Rahman, Priyanggo Karunia (English Education Department, 2022)
The aim of this study was to find out the significant difference of the skill in reading comprehension of narrative text between the students by using RCRR Strategy and those who are not. The subject of this study were the students of eighth grade students of a state high school in Kelapa district, Bangka Belitung province. In this study, the researcher used quantitative approach with quasi-experimental design.the findings showed that the result of mean score of post-test in the experimental group was higher (71.11) than the mean score in control group (60.29). Meanwhile, the result of independent samples test of students’ post–test between experimental and control group, the t-otained in equal variances assumed was 3.40 and the significant (2- tailed) was.001. Since the t-obtained was higher than t-table ((3.40>2.05)) and the significant (2-tailed) was lower than computation with level significant (.001<0.05). It could be concluded that there was a significant difference between the samples significantly, and RCRR Strategy improved the students’ skill in reading comprehension of narrative text. Therefore, the result of this study is expected to contribute to the development of the process of English teaching and learning, epecially for teaching and learning reading comprehension.